Ethical issues in international buyer–supplier relationships: a dyadic examination - Carter, Craig R (Journal of Operations Management, 2000)
Abstract The author combines extant literature with findings from focus group interviews and a set of surveys to identify the ethical issues involved in relationships of US purchasing managers and their non‐US suppliers. Survey data from matched sets (dyads) of buyers and suppliers is then used to examine the influence of unethical behavior on the satisfaction with the relationship and on supplier performance.